ChemInform Abstract: Light‐Driven Organocatalysis using Inexpensive, Nontoxic Bi2O3 as the Photocatalyst. Issue 8 (February 2015) - Riente, Paola; Matas Adams, Alba; Albero, Josep; Palomares, Emilio; Pericas, Miquel A.
Abstract The direct asymmetric alkylation of aldehydes (II) with α‐bromocarbonyl compounds is achieved in the presence of the combination of photocatalytic Bi2O3 and a chiral oxazolidinone catalyst.